The Impact of Social Capital on Socioeconomic Condition of Ckdu Patients in Sri Lanka: An Empirical Investigation - Premadasa, H K Salinda; Priyanath, H. M. S.; Walpita, C. N. (International Journal of Scientific Research and Management (IJSRM), 2020)
Chronic Kidney Disease of Uncertain aetiology (CKDu) has been the cause of devastation on patients, their families and the society alike in rural Sri Lanka. CKDu patients’ best hope for help lies in informal support of social mechanisms, due mainly to the absence of formal support mechanisms. Hence, this study attempted to explore how social capital affect the socio-economic condition of CKDu patients. Study mainly employed the survey method to gather data collected from 132 CKDu patients living in two villages in Rideemaliyadda. Data were collected using structural questionnaire having face-to-face interviews and analysed using Partial Least Squares-Structural Equation Modelling. Results revealed that relational social capital (RSC) plays a dominant role on the improvement of socio-economic conditions of CKDu patients. RSC has a positive significant impact on the flow of information and resources, which facilitate to improve socio-economic condition of CKDu patients. However, structural social capital (SSC) has no significant impact on the flow of information and resources, which affect the socio-economic condition of CKDu patients. Thus, this study conclude that social capital, especially RSC has a significant impact on the flow of information and resources and thereby improve the socio-economic condition of the CKDu patients in Sri Lanka.